OPTICAL SOLITONS TO THE CONFORMABLE TIME-FRACTIONAL PERTURBED RADHAKRISHNAN-KUNDU-LAKSHMANAN EQUATION - Sulaiman, Tukur Abdulkadir; Bulut, Hasan; Yel, Gulnur; Atas, Sibel Sehriban (Baku State Univ, Inst Applied Mathematics, 2018)
This study reaches the dark and singular optical solitons solutions to the time-fractional Radhakrishnan-Kundu-Lakshmanan equation. The parametric conditions that guarantee the existence of valid solitons and other solutions are stated. The reported solutions may be useful in expalining the physical meaning of the Radhakrishnan-Kundu-Lakshmanan equation and other related nonlinear models arising in nonlinear sciences.
6th International Conference on Control and Optimization with Industrial Applications (COIA) -- JUL 11-13, 2018 -- Baku, AZERBAIJAN
Keywords: Sinh-Gordon equation; optical soliton; fractional derivative